Effects of CuO nanoparticles as phase change material on chemical, thermal and mechanical properties of asphalt binder and mixture. (10th August 2020) - Amini, Nahid; Hayati, Parham
Highlights: Nano-CuO-modified asphalt binders increased the Cp of asphalt binders. The PCM eliminated the destructive bonds that caused short and long term aging. Nano-CuO as PCM decreased Tpc of the modified samples by 7 °C. CNTs as a conductive material could transfer the stored heat by Nano-CuO as a PCM. MCS was chosen as a combination with the optimum results. Abstract: Copper oxide nanopowders (Nano-CuO) as phase change material (PCM), Styrene-Butadiene-Styrene (SBS), and carbon nanotubes (CNTs) as a conductive material, were added separately and together in five combination designs to hot mix asphalt (HMA). Controlling the thermal energy transfer was achieved by using Nano-CuO. FTIR analysis illustrated that PCM eliminated the destructive bonds that caused short and long term aging in asphalt binder. From the DSR test results, it was deduced that the modified asphalt binders met the fatigue resistance limit. It was determined that the thermal energy storage (TES) in PCM-modified asphalt binders increased and, also glass transition temperature Tg significantly improved, melting peak temperature Tpm were higher than the pure asphalt binder, and crystallization peak temperature Tpc decreased by 7 °C. According to BBR test results, creep stiffness St and m-value for the modified asphalt binders adhere to the permissible limits at −6 °C. Nano-CuO-modified asphalt binders significantly increased the specific heat capacity Cp of asphalt binders and decreased the temperature and moisture susceptibility. Overall, the combination, including all the three additives, had the most acceptable properties.